IV models of ordered choice - Andrew Chesher; Konrad Smolinski (Centre for Microdata Methods and Practice (cemmap), 2009)
This paper studies single equation instrumental variable models of ordered choice in which explanatory variables may be endogenous. The models are weakly restrictive, leaving unspecified the mechanism that generates endogenous variables. These incomplete models are set, not point, identifying for parametrically (e.g. ordered probit) or nonparametrically specified structural functions. The paper gives results on the properties of the identified set for the case in which potentially endogenous explanatory variables are discrete. The results are used as the basis for calculations showing the rate of shrinkage of identified sets as the number of classes in which the outcome is categorised increases.
Keywords: C10; C14; C50; C51; 330; Endogeneity; Incomplete models; Instrumental variables; Ordered choice; Ordered Probit; Set Identification; Threshold Crossing Models; Instrumentalvariablen-Schätzmethode; Nichtparametrisches Verfahren; Probit-Modell; Modellierung; Theorie